1992
DOI: 10.1021/bi00152a044
|View full text |Cite
|
Sign up to set email alerts
|

Nature of the interaction of growth factors with suramin

Abstract: Suramin inhibits the binding of a variety of growth factors to their cell surface receptors. The direct interaction of suramin with acidic fibroblast growth factor has been detected by the enhancement of the drug's fluorescence in the presence of the protein with the maximum effect occurring at a molar ratio of suramin to aFGF of 2:1. This interaction stabilizes aFGF to thermal denaturation and partially protects a free thiol in its polyanion binding site from oxidation. The binding of suramin to aFGF also ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

12
89
1

Year Published

1994
1994
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 145 publications
(102 citation statements)
references
References 34 publications
12
89
1
Order By: Relevance
“…Similar effects have recently been reported with antibodies that block the activity of VEGF (Kim et al, 1993). The strong interaction of suramin with heparinbinding growth factors (Middaugh et al, 1992) suggests that the analogues may also be effective against other heparinbinding growth factors. It is notable that all of the bestcharacterised angiogenic factors are also heparin binding (e.g.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…Similar effects have recently been reported with antibodies that block the activity of VEGF (Kim et al, 1993). The strong interaction of suramin with heparinbinding growth factors (Middaugh et al, 1992) suggests that the analogues may also be effective against other heparinbinding growth factors. It is notable that all of the bestcharacterised angiogenic factors are also heparin binding (e.g.…”
Section: Discussionsupporting
confidence: 78%
“…A recent, detailed study of the interaction of suramin with growth factors has shown that it blocks acidic FGF (aFGF) activity by aggregation of the growth factor into suramin aFGF multimers, with an aFGF to suramin ratio of 2:1 (Middaugh et al, 1992 itself, e.g. FGF and PDGF (Hosang, 1985;Middaugh et al, 1992), or possibly to the growth factor receptor, it has other diverse activities that probably contribute to its antiproliferative and antimetastatic activities. These include, in the context of antiproliferation, inhibition of key enzymes involved in the intracellular transduction of mitogenic signals, e.g.…”
mentioning
confidence: 99%
“…Protein aggregation has been suggested to be a key process in the inhibition of FGFs mitogenic activity by suramins (27). In addition, these compounds have been proposed to block the interaction of aFGF with heparin, because it has been demonstrated that their anti-mitogenic activity can be reverted by this glycosaminoglycan (25,26).…”
Section: Discussionmentioning
confidence: 99%
“…The antiangiogenic activity of suramins is based, at least in part, on their ability to disrupt the interaction of many growth factors with their membrane receptors, such as in the case of FGFs and their tyrosine kinase receptors (19, 24 -26). Because it has been shown that heparin disrupts aFGF⅐suramin complexes (27) and counteracts the antiangiogenic effect of these polysulfonated ureas (25,26), suramins are considered to act by blocking the heparin-binding sites of FGFs (28). Another group of antiangiogenic and antitumoral compounds is comprised by suradistas, a type of noncytotoxic synthetic binaphthalene sulfonic distamycin-A derivatives.…”
mentioning
confidence: 99%
See 1 more Smart Citation